A computational study of the Fontan circulation with fenestration or hepatic vein exclusion. (1st October 2017) - Puelz, Charles; Acosta, Sebastián; Rivière, Béatrice; Penny, Daniel J.; Brady, Ken M.; Rusin, Craig G.
Abstract: Fontan patients may undergo additional surgical modifications to mitigate complications like protein–losing enteropathy, liver cirrhosis, and other issues in their splanchnic circulation. Recent case reports show promise for several types of modifications, but the subtle effects of these surgeries on the circulation are not well understood. In this paper, we employ mathematical modeling of blood flow to systematically quantify the impact of these surgical changes on extracardiac Fontan hemodynamics. We investigate two modifications: (1) the fenestrated Fontan and (2) the Fontan with hepatic vein exclusion. Closed–loop hemodynamic models are used, which consist of one–dimensional networks for the major vessels and zero–dimensional models for the heart and organ beds. Numerical results suggest the hepatic vein exclusion has the greatest overall impact on the hemodynamics, followed by the largest sized fenestration. In particular, the hepatic vein exclusion drastically lowers portal venous pressure while the fenestration decreases pulmonary artery pressure. Both modifications increase flow to the intestines, a finding consistent with their utility in clinical practice for combating complications in the splanchnic circulation. Highlights: Closed-loop vessel network models are used to study variations of the extracardiac Fontan physiology. Hemodynamics in the standard Fontan, fenestrated Fontan, and Fontan with hepatic vein exclusion are considered. Our results focus on the mesenteric and pulmonary circulations and on oxygen transport.